Germany’s Energiewende: A tale of increasing costs and decreasing willingness-to-pay - Andor, Mark A.; Frondel, Manuel; Vance, Colin (Technische Universität Dortmund, 2016)
This paper presents evidence that the accumulating costs of Germany’s ambitious plan to transform its system of energy provision – the so-called Energiewende – are butting up against consumers’ decreased willingness-to-pay (WTP) for it. Following a descriptive presentation that traces the German promotion of renewable energy technologies since 2000, we draw on two stated-preference surveys conducted in 2013 and 2015 that elicit the households’ WTP for green electricity. To deal with the bias that typifies hypothetical responses, a switching regression model is estimated that distinguishes respondents according to whether they express definite certainty in their reported WTP. Our results reveal a strong contrast between the households’ general acceptance of supporting renewable energy technologies and their own WTP for green electricity.
Discussion Paper / SFB823;31, 2016
Keywords: willingness-to-pay; consequential script; cheap talk; 310; 330; 620